2024
DOI: 10.3390/jpm14010125
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Exploring the Impact Factors for Intraocular Pressure Prediction in Myopic Children with Atropine Control Utilizing Multivariate Adaptive Regression Splines

Tzu-En Wu,
Jun-Wei Chen,
Tzu-Chi Liu
et al.

Abstract: Purpose: The treatment of childhood myopia often involves the use of topical atropine, which has been demonstrated to be effective in decelerating the progression of myopia. It is crucial to monitor intraocular pressure (IOP) to ensure the safety of topical atropine. This study aims to identify the optimal machine learning IOP-monitoring module and establish a precise baseline IOP as a clinical safety reference for atropine medication. Methods: Data from 1545 eyes of 1171 children receiving atropine for myopia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…This patient's anterior chamber was deeper than 3.5 mm in both eyes, and reportedly, atropine instillation can shorten the axial length but deepen the anterior chamber [14]; therefore, it is unlikely that the increased intraocular pressure was caused by the narrowing of the angle. In a large series of myopic children treated with atropine, Wu et al [15] reported that atropine may elevate intraocular pressure when its baseline level exceeds 14 mm Hg. The patient described in this case report had a high baseline intraocular pressure of 20/21 mm Hg, which may have increased his susceptibility to intraocular pressure elevation following atropine administration.…”
Section: Case Reports In Ophthalmologymentioning
confidence: 99%
“…This patient's anterior chamber was deeper than 3.5 mm in both eyes, and reportedly, atropine instillation can shorten the axial length but deepen the anterior chamber [14]; therefore, it is unlikely that the increased intraocular pressure was caused by the narrowing of the angle. In a large series of myopic children treated with atropine, Wu et al [15] reported that atropine may elevate intraocular pressure when its baseline level exceeds 14 mm Hg. The patient described in this case report had a high baseline intraocular pressure of 20/21 mm Hg, which may have increased his susceptibility to intraocular pressure elevation following atropine administration.…”
Section: Case Reports In Ophthalmologymentioning
confidence: 99%